Pengaruh Covid-19 Terhadap Kinerja Pembiayaan Kesejahteraan Pegawai (PKP) di Bank XYZ Syariah - Halimatun Sadiyah; Agus Rizal (Economic Reviews Journal, 2025)
This study aims to analyse the effect of the number of COVID-19 cases on the performance of employee welfare financing (PKP) at XYZ Sharia Bank in Indonesia. The background of this study stems from the economic disruption caused by the pandemic, which has affected consumption patterns, income stability, and the payment behaviour of formal sector employees. This study employs a quantitative approach using survey methods and primary data documentation involving 42 respondents who are users of the PKP product, and the data is analysed using simple linear regression through the SPSS version 24 software. The results indicate that the regression model Y=66.73+0.56X is statistically significant with a coefficient of determination R² = 0.554, meaning that 55.4% of the variation in PKP payment performance can be explained by the number of COVID-19 cases in the respondents' environment. The t-test significance value of 0.000 (< 0.05) reinforces the conclusion that the number of COVID-19 cases has a significant impact on payment performance. Empirically, these results indicate that the pandemic triggered adaptive policies from banks, such as restructuring and contract flexibility, which actually strengthened employee payment resilience. These findings contribute theoretically to the literature on Islamic finance during crises and encourage innovation in the design of more responsive financing performance in the context of systemic risk.